Hubungan Motivasi Keluarga Ibu Hamil dengan Keteraturan Mengkonsumsi Tablet Fe - Aditiya Alfa Martalisa (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
Provision of Fe tablets is an effort to prevent iron deficiency anemia in pregnancy, but this is often inhibited by the regularity of pregnant women to consume Fe tablets. The consumption of Fe tablets is strongly influenced by the motivation of the family of pregnant women. To prove that the administration of Fe tablets tends to have benefits, we want to examine the relationship between the motivation of families of pregnant women with regular consumption of Fe tablets. This research is an analytical study that is cross sectional. Samples taken with a simple random sampling technique were 34 respondents. Data collection using a questionnaire. To analyze the relationship, thetest was used chi square with α = 0.05. The results showed that for pregnant women with good motivation 73% of respondents regularly consumed Fe tablets, pregnant women with sufficient motivation were 8.8% regular, and 2.9% were not regularly consuming Fe tablets, pregnant women with motivation were less 8.8% regularly and 5.9% did not regularly consume Fe tablets. From the analysis of correlation Chi -Square with Pvalue = 0.001 at significance level α = 0.05 so that H0 is rejected means that there is a relationship of motivation families of pregnant women with regularity consuming Fe tablet. Based on the description above it can be concluded that family motivation is the dominant factor associated with regular consumption of Fe tablets.